Therapeutic Use of Limbal Stem Cells - Avunduk, Avni M.; Tekelioglu, Yavuz (Current Stem Cell Research & Therapy, 2006)
Stem cells are defined as relatively undifferentiated cells that have the capacity to generate more differentiated daughter cells. Limbal stem cells are responsible for epithelial tissue repair and regeneration throughout the life. Limbal stem cells have been localized to the Palisades of Vogt in the limbal region. Limbal stem cells have a higher proliferative potential compared to the cells of peripheral and central cornea. Limbal stem cells have the capacity to maintain normal corneal homeostasis. However, in some pathological states, such as chemical and thermal burns, Stevens-Johnson syndrome, and ocular pemphigoid limbal stem cells fail to maintain the corneal epithelial integrity. In such situations, limbal stem cell transplantation has been required as a therapeutic option. In unilateral disorders, the usual source of stem cells is the contralateral eyes, but if the disease is bilateral stem cell allografts have to be dissected from family members or cadaver eyes. The advent of ex vivo expansion of limbal stem cells from a small biopsy specimen has reduced the risk of limbal deficiency in the donor eye. Concomitant immunosuppressive therapy promotes donor-derived epithelial cell viability, but some evidences suggest that donor-derived epithelial stem cell viability is not sustained indefinitely. Thus, long-term follow-up studies are required to ascertain whether donor limbal stem cell survival or promotion of recolonization by resident recipient stem cells occurs in restored recipient epithelium. However, this is not an easy task since a definitive limbal stem cell marker has not been identified yet. This review will discuss the therapeutic usage of limbal stem cells in the corneal epithelial disorders.
Keywords: Limbal stem cells